The nature of civil conflict - Cemal Eren Arbath; Quamrul Ashraf; Oded Galor (Brown University, Department of Economics, 2013)
This research empirically establishes that the emergence, prevalence, and recurrence of civil conflict in the modern era reflect the long shadow of prehistory. Exploiting variations across contemporary national populations, it demonstrates that genetic diversity, as determined pre-dominantly tens of thousands of years ago, has contributed significantly to the frequency, incidence, and onset of both overall and ethnic civil conflicts over the last half century, accounting for a large set of geographical and institutional correlates of civil conflict, as well as measures of economic development. These findings arguably reflect the adverse effect of genetic diversity on interpersonal trust and cooperation, the potential impact of genetic diversity on income inequality, the potential association between genetic diversity and divergence in preferences for public goods and redistributive policies, and the contribution of genetic diversity to the degree of fractionalization and polarization across ethnic and linguistic groups in the population.
Keywords: 330